2004
DOI: 10.1520/jfs2003372
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Survey of Third Molar Development in Relation to Chronological Age Among Japanese Juveniles

Abstract: The aim of the present study was to establish Japanese reference material on the third molar development of Japanese juveniles for forensic application. Observations were performed on the orthopantomograms of 1282 Japanese patients between the ages of 14.0 and 24.0 years. Demirjian formation stages of the maxillary and mandibular third molars were recorded for chronological evaluation of wisdom teeth and applied for further statistical analysis. Statistically significant differences were noted between the uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
87
5
29

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(153 citation statements)
references
References 14 publications
28
87
5
29
Order By: Relevance
“…While our study shows that the relationship is higher in female than in male, the contrary result (r 2 in male=0.54, r 2 in female=0.45) is found by Prieto et al [8] There is high relationship (Table 5) between 18 and 28, 38 and 48 respectively, certified by other research [4,[8][9][10][11][12][13][14]. There is, however, no relationship between 18 and 48, 28 and 38.…”
Section: Discussioncontrasting
confidence: 77%
“…While our study shows that the relationship is higher in female than in male, the contrary result (r 2 in male=0.54, r 2 in female=0.45) is found by Prieto et al [8] There is high relationship (Table 5) between 18 and 28, 38 and 48 respectively, certified by other research [4,[8][9][10][11][12][13][14]. There is, however, no relationship between 18 and 48, 28 and 38.…”
Section: Discussioncontrasting
confidence: 77%
“…It is observed that the number of cases lacking age documentation and the number of unidentified cadavers and the human remains are increasing. In view of this, the need for age estimation is increasing day by day [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Durability of dental structure makes it one of the materials of choice in age estimation as compare to skeletal method, which is influenced by exogenous factors [2,5,[7][8][9][10]. Tooth or dentition being the hardest structure in the body survives every disaster such as fire accidents, bomb blast, plane crashes, mass disasters etc [7,8,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Design Methods were tested on a target sample of 300 dental panoramic radiographs (age [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Diagnostic accuracy was assessed on separate reference data (n = 1,663, age [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Root stage was the diagnostic test predicting 18 years of age.…”
Section: Introductionmentioning
confidence: 99%